PEMBUATAN PLANG EDUKASI LAMANYA SAMPAH ANORGANIK TERURAI DI DESA WATUNGGARANDU KECAMATAN LALONGGASUMEETO KABUPATEN KONAWE - Yusran, Sartiah; Bahar, Hartati; Findriyanti, Findri; Kombong, Oselya Meidy (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2024)
Trash is anything that is simply thrown away, and in many cases, it causes problems for the environment. A World Bank report shows that the amount of waste in cities around the world is expected to continue to increase by 70% from this year to 2025, from 1.3 billion tonnes per year to 2.2 billion tonnes per year. The largest increases occurred in cities in poor countries. Based on World Bank data, domestic waste generation in Indonesia is 151,921 tons per day, which means that each Indonesian resident throws away approximately 0.85 kilograms of waste every day. Based on the same data, only 80% of all waste produced globally is collected, while the rest is destroyed and pollutes the environment. From the results of a field survey carried out in Watungarandu Village, Lalonggasumeeto District, Konawe Regency, we found that there was still a lot of rubbish that was not disposed of properly, was thrown in random places and was also littered everywhere. This is what motivates us MD-MBKM KKN students in Watungarandu Village to provide education to create public awareness not to litter. The aim of installing this waste education sign is to provide awareness to the public about the dangers of waste that is thrown away carelessly. The trash sign itself explains how long it takes for the trash to decompose. The methods used are presentations and consultations. The results of this activity aim to increase public awareness of the dangers of littering and improve the welfare of the people of Watungarandu Village.